ISSUES OF READING CULTURE IN LITHUANIAN LIBRARIANSHIP inin 1918–1940 - SIBRIAN, INETA (Knygotyra, 2015)
The article the discusses theoretical and methodical premises of the culture of reading in 1918–1940 in Lithuania. The culture of reading is interpreted as a dual system of practical and intelectual abilities, required in the reading process. The subject is analysed with distinguishing between direct (propaganda of reading, books and library services, also informational, cultural and educational library services that intesify readership) and indirect methods (organisation of the system of libraries, gathering of reading materials, bibliographical work), elaborated in theoretical and methodical library science publications of Lithuanian and translated foreign authors. In Lithuanian publications, access to books and periodicals stand as the priority task of librarianship (V. Biržiška, J. Slapšinskas (Rimantas), V. Ruzgas). Authors described methods of working with readers, unfolding the content of direct and indirect education of readers. Propaganda of library services, books and reading, psychological judgement of the readership in the library, bibliographical work (V. Biržiška, V. Ruzgas, J. Slapšinskas (Rimantas), V. Ruzgas), appliation of sociological statistical research methods (V. Ruzgas, R. Burokas), policy of library collection supplement that matched the needs of the educational process and readers’ interests (V. Biržiška, R. Burokas, J. Slapšinskas (Rimantas) would make the core of Lithuanian culture of reading theory. Lithuanian authors mostly cited Russian pedagogues, psychologists (N. Rubakin, V. Vachterov, V. Vladislavlev (I. Gulbinski), V. Nevski and others). Methods of discretional (conscious, critical) reading were built according to the Western scientists (E. Faguet). There was also a special interest in the theory of self-education by Russian bibliopsychologist N. Rubakin. During the period under analysis, translations of the following authors were published: P. Ladewig’s textbook of librarianship, which included the basic knowledge of the culture of reading formation in libraries, N. Rubakin’s studies of science popularization and self-sustaining reading techniques, and articles by Western pedagogues, literary critics (G. Brandes, E. Dévaud and others) on the topical matters concerning reading.